Nanoparticles weaponized with built‐in functions for imaging‐guided cancer therapy. Issue 2 (20th May 2020) - Jing, Lihong; Yang, Chen; Zhang, Peisen; Zeng, Jianfeng; Li, Zhen; Gao, Mingyuan
Abstract: Imaging‐guided cancer therapy (IGCT) is rapidly emerging as a powerful precision cancer theranostic paradigm, as it can offer both diagnostic information and therapeutic benefits. But it relies on advanced theranostic agents that are largely constructed on top of nanomaterials. Conventionally, such theranostic agents are constructed by integrating different functional units, which will unnecessarily increase the size of the multi‐functional agents and inevitably encounter unwanted disassociation of the functional units in vivo, leading to false diagnosis and poor therapeutic efficacy. In this review, we highlight the state‐of‐the‐art progresses in biomedical applications of nanomaterials possessing built‐in functions suitable for cancer theranostic applications, particularly those who can convert near‐infrared (NIR) light into heat or radicals, as phototherapy holds remarkable promise for high‐precision cancer therapy. In addition, phototherapy can naturally be combined with photoacoustic imaging for realizing imaging‐guided therapy. In this context, the interactions between NIR and nanomaterials are classified and outlined. Then, different approaches for boosting imaging sensitivity and therapeutic efficacy, by improving the utilization of NIR light through different mechanisms, are discussed. Through examples on delineation and treatment of tumors in vivo, the opportunities and benefits of the theranostic nanoprobes for IGCT are highlighted. Moreover, the current challenges and future perspectives regarding both fundamental studies and clinical translation of the NIR‐mediated cancer theranostic agents are discussed. Abstract : Imaging‐guided cancer therapy (IGCT) holds remarkable promise for revolutionizing precision cancer theranostics, while it strongly relies on advanced theranostic agents that are largely constructed on top of nanomaterials. Nanoparticles with built‐in functions, particularly those who can naturally combine novel imaging with versatile phototherapies by converting near‐infrared (NIR) light into heat or radicals, are comprehensively summarized herein.